Työn määrä: Suomessa pitäisi tehdä enemmän työtä?; The Amount of Work: Why More Work Should Be Done in Finland? - Antti Kauhanen; Vesa Vihriälä (The Research Institute of the Finnish Economy (ETLA), 2016)
– The amount of work done in the economy has been subject to a lot of debate in Finland recently. Unemployment is considered a major problem. On the other hand, extending annual working time receives little support. In fact, a widely held view is that one should reduce the working time of the currently employed so that more people could be employed. The efforts of the Government to increase labour input, i.a. by reducing length of annual leave or the number of banking holidays are widely criticised. In the report we first describe how much work is done in Finland. Secondly, we recall the key messages of economics about the determination of labour input in a market economy. Thirdly, we endeavour to argue why, in the current Finnish circumstances, increasing the amount of work is useful and important, why the idea of work sharing is flawed, and why reducing labour costs makes sense.
Keywords: J2; J3; H5; E24; 330; Work; Labour input; Employment; Sustainability of public finances; Erwerbstätigkeit; Arbeitskosten; Öffentliche Finanzen; Nachhaltigkeit; Finnland